2018
DOI: 10.5830/cvja-2018-039
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a titration algorithm for de novo users of sacubitril/valsartan in a tertiary centre heart failure clinic

Abstract: Background: A reduction in the rate of death and hospitalisations in patients with heart failure (HF) with reduced ejection fraction receiving sacubitril/valsartan compared to enalapril was demonstrated in the PARADIGM-HF study. However, tolerability when initiating and optimising sacubitril/valsartan treatment in real clinical practice is unknown. Methods: We performed a prospective cohort study of clinical and biochemical parameters of the first 100 patients receiving sacubitril/valsartan in a tertiary HF cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The clinical importance of these data is that they reinforce the positive observations from the clinical trial data, and the emerging real world data, and indicate that the majority of the cohort of community patients can tolerate the agent and benefit from the compound, in terms of either a reduction in NT‐proBNP or an improvement in LVEF. More importantly, these data support the importance of achieving maximum dose and link this to a reduction in diuretic use, establishing clinical volume assessment as a critical feature in using this agent.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…The clinical importance of these data is that they reinforce the positive observations from the clinical trial data, and the emerging real world data, and indicate that the majority of the cohort of community patients can tolerate the agent and benefit from the compound, in terms of either a reduction in NT‐proBNP or an improvement in LVEF. More importantly, these data support the importance of achieving maximum dose and link this to a reduction in diuretic use, establishing clinical volume assessment as a critical feature in using this agent.…”
Section: Discussionmentioning
confidence: 52%
“…As observed from the PARADIGM sub-analysis by Jhund PS et al, when the authors assessed the efficacy and safety of sacubitril-valsartan by age, they found that the superiority of sacubitril-valsartan over enalapril persisted across all age groups including the elderly, though the same efficacy gap decreased slightly in the older population. 34 The clinical importance of these data is that they reinforce the positive observations from the clinical trial data, 1,33,35 and the emerging real world data, 14,15,17 and indicate that the majority of the cohort of community patients can tolerate the agent and benefit from the compound, in terms of either a reduction in NT-proBNP or an improvement in LVEF. More importantly, these data support the importance of achieving maximum dose and link this to a reduction in diuretic use, establishing clinical volume assessment as a critical feature in using this agent.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations